2013
DOI: 10.1111/jam.12306
|View full text |Cite
|
Sign up to set email alerts
|

Use of isothermal microcalorimetry to quantify the influence of glucose and antifungals on the growth of Candida albicans in urine

Abstract: Aims: Urinary tract infection (UTI) caused by Candida spp. is an increasing problem in clinical practice. Risk factors include diabetes mellitus, extremes of age, urinary tract abnormalities and indwelling catheters. Here, we determined the applicability of isothermal microcalorimetry (IMC) for the detection and antifungal drug susceptibility testing of Candida albicans in artificial urine. Methods and Results: Isothermal microcalorimetry was used to monitor the metabolic heat production rates of C. albicans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…in urine induced by addition of glucose in a concentration-dependent manner. This was consistent with a previous study (10); however, that study was conducted by using artificial urine and only one C. albicans strain. Our present study strengthened the previous observations in that: 1) the fungal growth acceleration was observed in natural urine derived from healthy donors as a result of adding glucose, and 2) this acceleration was observed in multiple C. albicans clinical isolates, in addition to C. krusei and C. glabrata.…”
supporting
confidence: 93%
“…in urine induced by addition of glucose in a concentration-dependent manner. This was consistent with a previous study (10); however, that study was conducted by using artificial urine and only one C. albicans strain. Our present study strengthened the previous observations in that: 1) the fungal growth acceleration was observed in natural urine derived from healthy donors as a result of adding glucose, and 2) this acceleration was observed in multiple C. albicans clinical isolates, in addition to C. krusei and C. glabrata.…”
supporting
confidence: 93%
“…The main advantage of this method in biofilm research is the opportunity to study them as entities as shown previously [ 18 ]. Over the last decade, the method has become more widely used in antimicrobial testing in various fields of medicine [ 19 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…IMC therefore detects enthalpy changes associated with the cell metabolism (see ΔH of equations 1–3) and has been used already to monitor microbial growth1516171819.…”
mentioning
confidence: 99%
“…In addition, metabolic reactions resulting from microbial proliferation emit heat which can be quantified continuously and non-invasively by isothermal micro-calorimetry (IMC). IMC therefore detects enthalpy changes associated with the cell metabolism (see ΔH of equations 1–3) and has been used already to monitor microbial growth 15 16 17 18 19 .…”
mentioning
confidence: 99%